Explosive spread of a neuroinvasive lineage 2 West Nile virus in Central Europe, 2008/2009 - Bakonyi, Tamás; Ferenczi, Emőke; Erdélyi, Károly; Kutasi, Orsolya; Csörgő, Tibor; Seidel, Bernhard; Weissenböck, Herbert; Brugger, Katharina; Bán, Enikő; Nowotny, Norbert (Veterinary microbiology, 2013)
For the first time outside sub-Saharan Africa, a lineage 2 West Nile virus (WNV) emerged in Hungary in 2004. It caused sporadic cases of encephalitis in goshawks (Accipiter gentilis), other predatory birds, and in mammals. As a consequence, a surveillance program was initiated in Hungary and in Austria, which included virological, molecular, serological and epidemiological investigations in human beings, birds, horses, and mosquitoes. The virus strain became endemic to Hungary, however only sporadic cases of infections were observed between 2004 and 2007. Unexpectedly, explosive spread of the virus was noted in 2008, when neuroinvasive West Nile disease (WND) was diagnosed all over Hungary in dead goshawks and other birds of prey (n=25), in horses (n=12), and humans (n=22). At the same time this virus also spread to the eastern part of Austria, where it was detected in dead wild birds (n=8). In 2009, recurrent WND outbreaks were observed in Hungary and Austria, in wild birds, horses, and humans in the same areas. Virus isolates of both years exhibited closest genetic relationship to the lineage 2 WNV strain which emerged in 2004. As we know today, the explosive spread of the lineage 2 WNV in 2008 described here remained not restricted to Hungary and Austria, but this virus dispersed further to the south to various Balkan states and reached northern Greece, where it caused the devastating neuroinvasive WND outbreak in humans in 2010.